Soft Gripper: Gecko‐Effect Inspired Soft Gripper with High and Switchable Adhesion for Rough Surfaces (Adv. Mater. Interfaces 18/2019). Issue 18 (23rd September 2019) - Tian, Hongmiao; Li, Xiangming; Shao, Jinyou; Wang, Chao; Wang, Yan; Tian, Yazhou; Liu, Haoran
Abstract : The ability of gecko climbing on rough surfaces can be attributed to the outstanding features of the "active adhesive" linked to natural coupling of toe muscles and surface adhesive structures, i.e., tuning the contact status between adhesive structures and opposite surfaces through muscles, which inspires us to firstly design active adhesive soft grippers with high/switchable adhesion for rough surfaces. More details can be found in article number1900875 by Hongmiao Tian, Jinyou Shao, and co‐workers.